Biomechanics of technique selection in women's artistic gymnastics - Manning, M. L. (Cardiff Metropolitan University, 2015)
Technique selection is fundamental to Women`s Artistic Gymnastics with rapidly evolving difficulty and complexity; a result of changes in the scoring system and apparatus design. The aim of this research was to increase knowledge and understanding of the biomechanics underpinning female longswing techniques to determine effective technique selection. Five progressive themes addressed this aim; contemporary trend analysis, biomechanical conceptual approach, method validation, biomechanical musculoskeletal approach and biomechanical energetic approach. Elite competition provided the basis to the thesis with a strong ecologically valid trend analysis reporting the straddle Tkachev as the most frequently performed release skill preceded by three distinct longswing techniques; arch, straddle, pike. Quantifying each technique through a biomechanical conceptual approach enumerated differences observed and examined their influence on key release parameters. Significant differences (p=0.05) were reported in the initiation and joint angular kinematics within the functional phases; however not for release parameters. Further examination into the joint kinetics and energetic demands of the gymnast were required to explain technique selection. Non-invasive methods of joint kinetic data collection are challenging within the elite competitive environment; therefore indirect methods were validated to provide confidence in the subsequent musculoskeletal approach. Inverse dynamic estimations were most sensitive to kinematic inputs with field versus lab comparisons highlighting systematic differences in joint moments (0.8%RMSD in consistency). Joint kinetics provided new knowledge of the underlying biomechanics of varying techniques, specifically greater shoulder joint moments and hip joint powers during the pike longswing. Examining gymnast energetic contribution to the total gymnast-high-bar energy system developed a novel effectiveness score highlighting the potential energy excess available to the arch (30%) and straddle (2%) techniques, indicating the potential to develop more complex versions of skills. This research provides coaches and scientists with specific physical preparation requirements for varying longswing techniques and insight into the need for customised technique selection.